Hedging the risk of oil - Tong, Man Chi (2006)
Abstract This paper studies the hedging activities of oil. More particularly, I investigate the case study example of British Airways (BA). The issues that examined in this paper include what types of risk BA is facing, the types of financial derivative instruments BA's using to hedge against its risks, effectiveness of BA's hedging, the extent of its derivatives usage, and a numerical example showing derivative instruments can be used to hedge against the movement of oil price risk and which derivative is more effective. I found out that the use of financial derivatives by BA is for hedging purpose, but not for speculative or trading purposes. BA is facing financing and interest rate risk, foreign exchange risk, fuel price risk, credit risk and other risks. Therefore, BA employs a mixture of swaps, options, forward and futures to hedge against these risks. The Group uses forward foreign exchange contracts to hedge against near-term foreign exchange risk, uses interest rate swaps to hedge against financing and interest rate risks, and uses a number of derivatives that are available the over the counter markets (such as options and forward contracts). During the financial year of 2006, the derivatives used by BA were generally found to be effective. Moreover, a numerical example is used to show how forward/futures and options can protect BA against the movement of fuel price risk. More importantly, using this example, I found out that BA is better off by using option market hedge.